PENGARUH BIAYA PROMOSI DAN BIAYA DISTRIBUSI TERHADAP PENINGKATAN PENJUALAN - samsul, samsul (COMPETITIVE, 2023)
this study aims to: (1) determine the effect of promotional costs on increasing sales in manufacturing companies listed on the IDX. (2) Knowing the effect of distribution costs on increasing sales in manufacturing companies listed on the IDX. (3) Knowing the effect of promotion costs and distribution costs simultaneously on increasing sales in manufacturing companies listed on the IDX. The object of this research is 15 manufacturing companies listed on the IDX. Data taken for 6 years from 2014 - 2019 and calculations using annual data consisting of: promotion costs, distribution and sales costs. Data collected by documentation method obtained through the official website. The data analysis tools used are linear regression analysis classical assumption test and hypothesis testing. Results shows that: (1) there is a significant positive effect of promotion costs on increasing sales with a t-count value of 2.069 which is greater than t-table 2.040 with a significance value of 0.047; (2) there is a positive and significant effect distribution costs to increase in sales with a t value of 2.252 which is greater than the t-table value of 2.040 with a value of significance 0.032; (3) There is a significant positive effect between promotion costs and distribution costs simultaneously to the increase in sales with a calculated F value of 4.197 which is greater than the F table of 3.32 with a significant value of 0.025.